(3GdTQWI GdYQHjI (B:s (3JCUjdG JGQjNjG, hJWhQG acQjG, hefXhQG eSJbHdjG (B= Arabic police : Intellectual development & future vision historical foundation /s - (3YHO GdeWdH, eeOhM YHO GdMejO,s 1955- ((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3TQWI GdTGQbI, eQcR HMhK GdTQWI,s, 2008)
(3jJfGhd cJGH (B((3GdTQWI GdYQHjI (B: (3JCUjdG JGQjNjG, hJWhQG acQjG, hefXhQG eSJbHdjG(B) (3hGdPj bGe HJCdjag (B((3eeOhM YHO GdMejO YHO GdeWdH(B) (3aj MhGdj (B(279) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdTQWI GdYQHjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3GSJQGJLjGJ hfXQjGJ GdYed GdTQWj, GdaUd GdKGfj (B: (3eSJbHd GdJYdje GdTQWj GdYQHj, GdaUd GdKGdK (B: (3GdJfHD GdCefj aj YUQ GdYhdeI, GdaUd GdQGHY (B: (3GdJOGHjQ GdTQWI dehGLgI GdNWhQI GdCefjI, GdaUd GdNGeS (B: (3GdYed GdTQWj YUQ GdeYdheGJ, GdaUd GdSGOS (B: (3EOGQI GdeYQaI GdCefjI(B.s
(3eSJNdU HGddZI GdEfLdjRjI (B: (3UaMI (B278-279.s
Keywords: (3GdTQWIs -- (3GdHdGO GdYQHjIs -- (3JGQjNs; (3GdCef GdOGNdjs -- (3GdHdGO GdYQHjIs -- (3JGQjNs; (3GdTQWI GdEOGQjIs -- (3GdHdGO GdYQHjIs